Strategy To Increase Customer Satisfaction Based On Service Quality - Silaningsih, Endang; Tjahja Andari, Titiek; Rihadatul Aisy, Zahro (International Journal of Science, Technology & Management, 2024)
The purpose of this research is to determine and analyze how the affect of service quality (reliability, responsiveness, assurance, empathy, tangible) simultaneously and partially on customer satisfaction, customer satisfaction level index, and implementation and performance strategies of PT Jayamandiri Gemasejati Bogor. This research uses quantitative data and primary data types through distributing questionnaires using a Likert scale. The sample in this research distributrd to 100 people with non-probability sampling technique, namely accidental sampling. The method used in this research is multiple linear regression analysis. The results showed that in the simultaneous test results (f test) it was found that the independent variables of reliability, assurance, empathy, responsiveness, and Tangible simultaneously had a positive and significant affect on customer satisfaction and for the partial test results (t test) it is found that the variables of reliability, responsiveness, and assurance have a positive and significant affect on customer satisfaction, respectively At the same time, the variables of empathy and tangible partially are not having a positive and significant affect on customer satisfaction.. The result of the Customer Satisfaction Index (CSI) score of service quality is 68.25%. The implementation strategy uses important performance analysis (IPA), the strategy is a) Make continuous improvements so that performance attributes increase b) Maintaining so that the performance does not decrease c) This quadrant must be seriously managed because it usually causes customer disappointment d) Evaluate all excessive activities.